2015
DOI: 10.1007/s11119-015-9407-8
|View full text |Cite
|
Sign up to set email alerts
|

Use of multi-spectral airborne imagery to improve yield sampling in viticulture

Abstract: The wine industry needs to know the yield of each vine field precisely to optimize quality management and limit the costs of harvest operations. Yield estimation is usually based on random vine sampling. The resulting estimations are often not precise enough because of the high variability within vineyard fields. The aim of the work was to study the relevance of using NDVI-based sampling strategies to improve estimation of mean field yield. The study was conducted in nine non-irrigated vine fields located in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 25 publications
3
51
0
1
Order By: Relevance
“…Compared to the other sampling schemes, SRS (scheme A) obtained the greatest inaccuracy in estimating the yield (almost 10%). However, this value could be considered as acceptable given the criterion adopted by other researchers (Carrillo et al, 2016). When stratifying the samples using the NDVI or the ECa, the sample means worked even better achieving very good accuracy values below 2% (Table 1).…”
Section: Sampling To Estimate Yieldmentioning
confidence: 93%
See 1 more Smart Citation
“…Compared to the other sampling schemes, SRS (scheme A) obtained the greatest inaccuracy in estimating the yield (almost 10%). However, this value could be considered as acceptable given the criterion adopted by other researchers (Carrillo et al, 2016). When stratifying the samples using the NDVI or the ECa, the sample means worked even better achieving very good accuracy values below 2% (Table 1).…”
Section: Sampling To Estimate Yieldmentioning
confidence: 93%
“…As NDVI is related to vine vigour, the method is a way of distributing sampling points by covering the areas of different vigour to capture vineyard canopy variability within the plot. This same idea is behind the method proposed by Carrillo et al (2016) to improve yield estimates, also in viticulture. The authors concluded with the need to consider a two-step sampling method combining NDVI-based sampling with random vine sampling to apply each strategy to predict a specific component of the productive potential of the vineyard.…”
Section: Introductionmentioning
confidence: 92%
“…It must be clear that the objective of this technical note is not to provide an explanation for the observed NDVI spatial variability. Much work has already been dedicated to this issue in the literature (Acevedo-Opazo et al, 2008;Carrillo et al, 2016;Hall et al, 2002;Johnson et al, 2001). The objective is rather to discuss what seems to be observable and provide areas for further investigation.…”
Section: Practical Temporal Resolution Of Sentinel-2 Imagesmentioning
confidence: 99%
“…Multiple studies have shown the interest of remote sensing images for field or within-field management purposes in viticulture such as irrigation or fertilization monitoring (Acevedo-Opazo et al, 2008;Carrillo et al, 2016;Hall et al, 2002;Johnson et al, 2001). However, current limitations of most remote sensing acquisition platforms are their low temporal resolution (16 days for the LandSat8 platform) and their cost ($1.65/km² for Spot 6-7 new image acquisition with a minimum order of 500km² or $1.28/km² for RapidEye new image acquisition with a minimum order of 3500km²).…”
Section: Introductionmentioning
confidence: 99%
“…It is undeniable that the factor that has exponentially encouraged the spread of UAV application in agriculture is the continuous advance in sensor technologies, providing higher resolution, lower weight and dimensions, and cost reduction [23,[25][26][27][28]. Several authors describe a wide range of UAV applications for PV purposes: vigor and biomass [29][30][31][32][33][34], yield and quality monitoring [35,36], water stress [37][38][39][40][41], canopy management [42], diseases [43][44][45][46], weeds [47][48][49], and missing plants [50][51][52][53].…”
Section: Introductionmentioning
confidence: 99%